2007
DOI: 10.1029/2007gl031296
|View full text |Cite
|
Sign up to set email alerts
|

Separating the effects of albedo from eco‐physiological changes on surface temperature along a successional chronosequence in the southeastern United States

Abstract: [1] In the southeastern United States (SE), the conversion of abandoned agricultural land to forests is the dominant feature of land-cover change. However, few attempts have been made to quantify the impact of such conversion on surface temperature. Here, this issue is explored experimentally and analytically in three adjacent ecosystems (a grass-covered old-field, OF, a planted pine forest, PP, and a hardwood forest, HW) representing a successional chronosequence in the SE. The results showed that changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
226
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(242 citation statements)
references
References 21 publications
14
226
1
1
Order By: Relevance
“…During the growing season, these two forests are not very different. During the non-growing season, transpiration from evergreen forests may be higher than that from deciduous forests [11]. This means that the cooling effect caused by ET in evergreen forests is greater than that in deciduous forests.…”
Section: Discussionmentioning
confidence: 93%
“…During the growing season, these two forests are not very different. During the non-growing season, transpiration from evergreen forests may be higher than that from deciduous forests [11]. This means that the cooling effect caused by ET in evergreen forests is greater than that in deciduous forests.…”
Section: Discussionmentioning
confidence: 93%
“…The marginal distribution sampling (MDS) filling method is based on Reichstein et al (2005), and the ERA-Interim filling method can be found in Vuichard and Papale (2015 ration (ET), and land surface temperature changes due to historical LULCC (Boisier et al, , 2014 and the climatic effects of forest (Li et al, 2015). Meanwhile, the development of FLUXNET (Baldocchi et al, 2001) enables the study of land surface responses to different land-cover types based on paired field observations from neighboring flux towers over forest and open land (Juang et al, 2007;Lee et al, 2011;Luyssaert et al, 2014;Teuling et al, 2010;Williams et al, 2012). In terms of LSM evaluation, the paired site observations have been mainly used to simulated impacts of LULCC on land surface temperature (Chen and Dirmeyer 2016;Lejeune et al, 2016;Vanden Broucke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This feedback is crucial in the model predictions; without it other biophysical processes may overwhelm the albedo effect to generate warming instead 5 . Ongoing land-use activities, such as land management for climate mitigation, are occurring at local scales (hectares) presumably too small to generate the feedback, and it is not known whether the intrinsic biophysical mechanism on its own can change the surface temperature in a consistent manner 6,7 . Nor has the effect of deforestation on climate been demonstrated over large areas from direct observations.…”
mentioning
confidence: 99%
“…Forests have lower surface albedo than shrubs, grasses and pastures 6,7,14 . Deforestation decreases the net shortwave absorption by an amount DS that depends in part on climate regimes.…”
mentioning
confidence: 99%